2012
DOI: 10.1007/s10924-012-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Green Composites Based on Tapioca Starch and Differently Recycled Paper Cellulose Fibers

Abstract: Green composites obtained from biodegradable renewable resources have gained much attention due to environmental problems resulting from conventionally synthetic plastics and a global increasing demand for alternatives to fossil resources. In this work we used different cellulose fibers from used office paper and newspaper as reinforcement for thermoplastic starch (TPS) in order to improve their poor mechanical, thermal and water resistance properties. These composites were prepared by using tapioca starch pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
2
27
0
3
Order By: Relevance
“…The peaks at 1,514 and 1,252 cm 21 in untreated bagasse represent the aromatic C 5 C stretch of aromatic rings of lignin. In cellulose nanofiber spectra, peak at 1,252 and 1,514 cm 21 is not present which indicate most of the lignin was removed and pure cellulose was isolated. The increase of the band at 898 cm 21 in CNF spectra obtained from chemically treated bagasse indicates the typical structure of cellulose and peak at 670 cm 21 is for C-O-H out-ofplane bending mode in cellulose.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The peaks at 1,514 and 1,252 cm 21 in untreated bagasse represent the aromatic C 5 C stretch of aromatic rings of lignin. In cellulose nanofiber spectra, peak at 1,252 and 1,514 cm 21 is not present which indicate most of the lignin was removed and pure cellulose was isolated. The increase of the band at 898 cm 21 in CNF spectra obtained from chemically treated bagasse indicates the typical structure of cellulose and peak at 670 cm 21 is for C-O-H out-ofplane bending mode in cellulose.…”
Section: Resultsmentioning
confidence: 96%
“…The peaks at around 1,154 and 1,079 cm 21 were characteristic of C-O-H in starch, while the peak at 1,029 cm 21 was characteristic of the anhydroglucose ring O-C stretch [24]. The region below 800 cm 21 exhibited complex vibrational modes due to the skeletal mode vibrations of the pyranose ring in the glucose unit. It was observed that the relative peak strength of stretching vibrations for -OH groups in the FTIR spectra of composite films weakened with increase in % CNFs in the composite, indicating the hydrogen bonding between starch molecules was partially destroyed [4].…”
Section: Characterization Of Cellulose Nanofibril Reinforced Tps Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the bio-degradability of the newly synthesised composites as reported method, 21 with some minute alternations was adopted, in this study. Briefly, test specimens about 30×30×1 mm in sizes were cut from each of the composite, dried and 105 equilibrated at room temperature in desiccators, and weighed to determine the reference weight (control).…”
Section: Evaluation Of Soil Burial Degradationmentioning
confidence: 99%
“…The biodegradability of the P(3HB)-EC and CA-g-P(3HB)-EC composites was evaluated using soil burial test as-described earlier by Wattanakornsiri et al [18]. The soil burial test lasted for 6 weeks (42 days).…”
Section: Soil Burial Testmentioning
confidence: 99%